Performance Comparison of FBMC-OQAM and CP-OFDM Using AWGN Channel - Anggun Fitrian Isnawati; Dhia Fikri Zam Zami; M. Lukman Leksono (JURNAL NASIONAL TEKNIK ELEKTRO, 2023)
The 5G NR network planning covers the types of use scenarios and applications that include Enhanced Mobile Broadband (eMBB), Ultra-Reliable and Low Latency Communications (URLLC), and Massive Machine Type Communications (MTC). Regarding multicarrier modulation schemes, Orthogonal Frequency Division Multiplexing (OFDM) has become the most popular choice in previous technology, so OFDM is a strong candidate for its 5G NR technology application. However, OFDM has disadvantages such as higher PAPR and decreased bandwidth efficiency due to the addition of CP. These weaknesses can be overcome by the FBMC modulation scheme with Offset Quadrature Amplitude Modulation (OQAM) as a more efficient CP replacement for its implementation in 5G NR. This study analyzed the development of OQAM in Filter Bank multicarrier (FBMC) and compared it with using Cyclic Prefix (CP) based on OFDM using the AWGN channel. The first step of this research is to present an overview of the modulation scheme used. Next, compare the performance of FBMC-OQAM and CP-OFDM by analyzing several Bit Error Rate (BER) simulation results against the SNR value when both systems use the same simulation parameters. Based on the test results of each BER, both methods have different values, almost 2 dB for the same BER results. It indicates that the FBMC-OQAM system reached the BER value of 10-4 at SNR 15 dB. The CP-OFDM system, meanwhile, was able to achieve a BER value of 10-4 at SNR 17 dB. These results indicate that the FBMC-OQAM system is superior to CP-OFDM based on the BER values.